Konsep Merdeka Belajar Bagi Anak Usia Dini Perspektif Ki Hajar Dewantara - Masliyana; Muhammad Nasir (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Widya Gama Mahakam Samarinda, 2023)
The concept of independent learning is a concept that emphasizes the ability to think independently. Merdeka is here aimed at providing educators, students and parents with comfort and enjoyment in learning to facilitate innovation and creativity. This is based on the fact that individuals with an independent disposition are more likely to experience freedom in using their innate abilities effectively. Talking about the concept of freedom to learn is actually not something new, but has been propagated for a long time by Ki Hajar Dewantara. The ideas and concepts put forward by him have contributed to the formation of a more organized and well-defined framework in the field of education in Indonesia. However, in reality, currently it can be said that the quality of education still needs to be improved, especially in Early Childhood Education Institutions. So the aim of the research was to describe the concept of independent learning for young children from the perspective of Ki Hajar Dewantara. This research uses qualitative methodology, namely descriptive analysis which includes library research. Research findings show that freedom to learn is one of the efforts to achieve humanist education. One of the educational ideas that is very important to be disseminated in the learning practices of the society 5.0 era. According to Ki Hajar Dewantara, the presence of free learning for young children fosters a sense of unlimited freedom in carrying out play activities. Children will freely explore as an indication that children have physical and psychological independence. Not only that, Ki Hajar Dewantara included the concept of freedom of learning as one of the five basic principles of Panca Dharma which includes